The Effects of Crack on the Transmission Matrix of Rotor Systems. (2011) - Peng, Z.K.; Lang, Z.Q.; Meng, G.; Chu, F.L.
Abstract : The dynamic behavior of rotor containing crack is a subject of particular interest and has been extensively investigated by researchers. The effects of crack on the natural frequencies and modal shapes and motion orbits of rotor systems have already been well explored by researchers. In the present study, the infl uence of crack on the transmission matrices of the rotor systems is investigated by using the FEM (finite element method) analysis and the HBM (harmonic balance method) technique. It is for the first time revealed that there are differences between the transmission matrices for the fundamental frequency components and the transmission matrices for the super-harmonic components, and the differences are mainly determined by the crack location. The results are validated by numerical experiments where the system responses of a rotor system are obtained using Runge-Kutta method. The results are of significance for the development of effective crack detection methods in practice.